Rizofiltrasi Logam Pb (Plumbum) pada beberapa Jenis Tumbuhan Air - Elly Proklamasiningsih; Hernayanti Hernayanti (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2010)
The research about rhizofiltration of Pb in several species of aquatic plant had been conducted in a greenhouse of Biology Faculty, Jenderal Soedirman University. The aims of this research were to evaluate the aquatic plant species which has Pb accumulative characteristic and to determine Pb concentration tolerated by those plants. This research was used experimental method with split plot design. The main plot was kind of aquatic plant of Hydrilla verticillata (L.f), Pistia stratiotes L, and Salvinia molesta D.S.Mitchell. The Pb (NO3)2 concentrations of 0, 5, 10, 15 mg/l were as sub plot.   Each treatment was replicated for 3 times. The parameter observed were biomass (raw weight and dry weight), the Pb absorbed whether in root and shoot, and chlorophyll content. Data collected were analyzed using F test continued by LSD. The result of this research showed that both Pistia and Salvinia planted in 10 mg/l media were able to accumulate high Pb concentration. However, Pistia were able to accumulate Pb concentration mostly in root and only part be translocated in shoot. Whereas Salvinia was able to translocate Pb concentration in shoot higher than those in of Pistia.  The implications of these results for rhizofiltration are discussed.